Fostamatinib for the treatment of adult persistent and chronic immune thrombocytopenia: Results of two phase 3, randomized, placebo‐controlled trials. Issue 7 (15th May 2018) - Bussel, James; Arnold, Donald M.; Grossbard, Elliot; Mayer, Jiří; Treliński, Jacek; Homenda, Wojciech; Hellmann, Andrzej; Windyga, Jerzy; Sivcheva, Liliya; Khalafallah, Alhossain A.; Zaja, Francesco; Cooper, Nichola; et al.
Abstract: Spleen tyrosine kinase (Syk) signaling is central to phagocytosis‐based, antibody‐mediated platelet destruction in adults with immune thrombocytopenia (ITP). Fostamatinib, an oral Syk inhibitor, produced sustained on‐treatment responses in a phase 2 ITP study. In two parallel, phase 3, multicenter, randomized, double‐blind, placebo‐controlled trials (FIT1 and FIT2), patients with persistent/chronic ITP were randomized 2:1 to fostamatinib ( n = 101) or placebo ( n = 49) at 100 mg BID for 24 weeks with a dose increase in nonresponders to 150 mg BID after 4 weeks. The primary endpoint was stable response (platelets ≥50 000/μL at ≥4 of 6 biweekly visits, weeks 14‐24, without rescue therapy). Baseline median platelet count was 16 000/μL; median duration of ITP was 8.5 years. Stable responses occurred in 18% of patients on fostamatinib vs. 2% on placebo ( P = .0003). Overall responses (defined retrospectively as ≥1 platelet count ≥50 000/μL within the first 12 weeks on treatment) occurred in 43% of patients on fostamatinib vs. 14% on placebo ( P = .0006). Median time to response was 15 days (on 100 mg bid), and 83% responded within 8 weeks. The most common adverse events were diarrhea (31% on fostamatinib vs. 15% on placebo), hypertension (28% vs. 13%), nausea (19% vs. 8%), dizziness (11% vs. 8%), and ALT increase (11% vs. 0%). Most events were mild or moderate and resolved spontaneously or with medical management (antihypertensive, anti‐motility agents). Fostamatinib produced clinically‐meaningful responses in ITP patients including those who failed splenectomy, thrombopoietic agents, and/or rituximab. Fostamatinib is a novel ITP treatment option that targets an important mechanism of ITP pathogenesis.